X‐ray crystal structure of anhydrous chitosan at atomic resolution. Issue 7 (July 2016) - Naito, Philip‐Kunio; Ogawa, Yu; Sawada, Daisuke; Nishiyama, Yoshiharu; Iwata, Tadahisa; Wada, Masahisa
ABSTRACT: We determined the crystal structure of anhydrous chitosan at atomic resolution, using X‐ray fiber diffraction data extending to 1.17 Å resolution. The unit cell [a = 8.129(7) Å, b = 8.347(6) Å, c = 10.311(7) Å, space group P21 21 21 ] of anhydrous chitosan contains two chains having one glucosamine residue in the asymmetric unit with the primary hydroxyl group in the gt conformation, that could be directly located in the Fourier omit map. The molecular arrangement of chitosan is very similar to the corner chains of cellulose II implying similar intermolecular hydrogen bonding between O6 and the amine nitrogen atom, and an intramolecular bifurcated hydrogen bond from O3 to O5 and O6. In addition to the classical hydrogen bonds, all the aliphatic hydrogens were involved in one or two weak hydrogen bonds, mostly helping to stabilize cohesion between antiparallel chains. © 2016 Wiley Periodicals, Inc. Biopolymers 105: 361–368, 2016.